Kegiatan Taman Baca Untuk Meningkatkan Minat Baca Anak Di Tenggilis Mulya - Afandi, Nihro; Camelia, Naila Septiana; Maulidah, Ayu Mubarokatum (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
The reading garden activity in Tenggilis Mulya was conducted to increase children's reading interest, which remains low due to the dominance of gadget use and limited literacy facilities. Using the Participatory Action Research (PAR) approach, the program engaged children, parents, and volunteers to create a fun and interactive literacy environment. Weekly activities included shared reading sessions, discussions, and educational games. The results showed improved reading interest among children, active parental involvement, and a growing collective awareness of the importance of a literacy culture. Challenges such as weather and participant attendance remain, but overall, the program has proven to be an effective alternative literacy solution. The reading garden not only enhances reading skills but also helps shape children's character and learning spirit.